Introducing voluntary private health insurance in a mixed medical economy: are Hong Kong citizens willing to subscribe? - Alex Jingwei He (BMC, 2017)
Abstract Background Struggling to correct the public-private imbalance in its health care system, the Hong Kong SAR Government seeks to introduce a government-regulated voluntary health insurance scheme, or VHIS, a distinctive financing instrument that combines the characteristics of private insurance with strong government regulation. This study examines citizens' responses to the new scheme and their willingness to subscribe. Methods First-hand data were collected from a telephone survey that randomly sampled 1793 Hong Kong adults from September 2014 to February 2015. Univariate and multivariate methods were employed in data analysis. Results More than one third of the respondents explicitly stated intention of subscribing to the VHIS, a fairly high figure considering the scheme's voluntary nature. Multivariate analysis revealed moderate evidence of adverse selection, defined as individuals' opportunistic behaviors when making insurance purchasing decision based on their own assessment of risks or likelihood of making a claim. Conclusion The excellent performance of Hong Kong's public medical system has had two parallel impacts. On the one hand, high-risk residents, particularly the uninsured, do not face a pressing need to switch out of the overloaded public system despite its inadequacies; this, in turn, may reduce the impact of adverse selection that may lead to detrimental effects to the insurance market. On the other hand, high satisfaction reinforces the interests of those who have both the need for better services and the ability to pay for supplementary insurance. Furthermore, the high-risk population demonstrates a moderate interest in the insurance despite the availability of government subsidies. This may offset the intended effect of the reform to some extent.